2014
DOI: 10.1111/jabr.12028
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Minnesota Multiphasic Personality Inventory‐2‐Restructured Form (MMPI‐2‐RF) Scores, Workers' Compensation Status, and Spine Surgery Outcome

Abstract: This study examines whether workers' compensation (WC) patients respond more poorly to spine surgery than non-WC patients and whether poorer outcome is associated with individual differences in personality and emotional variables, as assessed by the Minnesota Multiphasic Personality Inventory-2-Restructured Form (MMPI-2-RF). Three-hundred eighty-two patients underwent presurgical psychological screening that included a diagnostic interview and psychometric testing. Pain level, functional ability, work status, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 36 publications
3
21
0
Order By: Relevance
“…MMPI-2-RF scales in this domain that were found to be associated with poorer outcome assess feelings of being overwhelmed, highly distressed, and dissatisfied with life, in addition to an inability to experience positive emotions, higher levels of anxiety and anger, and lack of self-confidence. Higher scores on these scales have also been to be associated with adverse outcomes of spine surgery (Block et al, 2014; Marek, Block, et al, 2015), as well as with higher levels of negative affect and maladaptive eating behaviors at 3 months following bariatric surgery (Marek, Ben-Porath, Merrell, Ashton, & Heinberg, 2014). Patients with these symptoms are likely to have problems with motivation and with recognition of treatment gains, whereas patients who do not experience such issues tend to have better SCS results.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MMPI-2-RF scales in this domain that were found to be associated with poorer outcome assess feelings of being overwhelmed, highly distressed, and dissatisfied with life, in addition to an inability to experience positive emotions, higher levels of anxiety and anger, and lack of self-confidence. Higher scores on these scales have also been to be associated with adverse outcomes of spine surgery (Block et al, 2014; Marek, Block, et al, 2015), as well as with higher levels of negative affect and maladaptive eating behaviors at 3 months following bariatric surgery (Marek, Ben-Porath, Merrell, Ashton, & Heinberg, 2014). Patients with these symptoms are likely to have problems with motivation and with recognition of treatment gains, whereas patients who do not experience such issues tend to have better SCS results.…”
Section: Discussionmentioning
confidence: 99%
“…Participants rated the intensity of emotions they experienced on Likert-type scales ( Not at all to Extremely ), and pain on a 0 to 10 Likert-type scale (higher value indicating more pain). Exploratory factor analyses indicated that the current emotional state items can be aggregated into two scales: Negative Affect and Positive Affect (Block et al, 2014; Marek, Block, et al, 2015). We used the Negative Affect scale in the current investigation because it was marked by items such as depressed mood, worry, anger, and fear.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 13 ]; Block, Marek, Ben-Porath and Ohnmeiss [ 24 ]) has found that elevated scores on the demoralization scale, RCd, are strongly correlated with poorer results at six months post spine surgery, including less improvement in pain and in self-reported physical disability, lower return to work rates, greater use of opioid medication, poorer satisfaction with surgical outcome, and worse overall outcome. Further, specific components of demoralization assessed by the MMPI-2-RF, including scales measuring Helplessness/Hopelessness, Self-Doubt and Inefficacy (a belief that one is incapable of making decisions and coping with difficulties), are significantly associated with poorer satisfaction and reduced results of both spine surgery (Block, Ben-Porath, Marek and Ohnmeiss [ 24 ]) and poorer results of spinal cord stimulation (Block, Marek, Ben-Porath and Kukal [ 12 ]). Further, scale RCd, is the only MMPI-2-RF scale associated with poor results in all the outcome areas assessed.…”
Section: Demoralizationmentioning
confidence: 99%
“…Certainly, my own research (see Block [ 10 ]) as well as that of others (Voorhies et al [ 16 ]; denBoer et al [ 43 ]), which has been focused on assessment of psychological “risk” factors, continues to demonstrate how specific psychological characteristics can undo even the most effective surgical intervention. We (Block, Marek, Ben-Porath and Ohnmeiss [ 24 ]) have found that, in addition to demoralization, several other characteristics assessed by the MMPI-2-RF are strongly correlated with reduced spine surgery results, including somatic sensitivity and malaise (Scales RC1 and MLS), low positive emotion (scale RC7), family problems (FML), social avoidance (SAV), and the PSY-5 scale negative emotionality/neuroticism (NEGE-r). However, the complexity of human nature is such that individuals may have strengths—traits, behaviors and emotional states--that can counteract more negative characteristics.…”
Section: Psychological “Maximizing” Factorsmentioning
confidence: 99%